2011
DOI: 10.1007/s00122-011-1762-x
|View full text |Cite
|
Sign up to set email alerts
|

Breeding maize as biogas substrate in Central Europe: II. Quantitative-genetic parameters for inbred lines and correlations with testcross performance

Abstract: Breeding maize for use as a biogas substrate (biogas maize) has recently gained considerable importance. To optimize hybrid breeding programs, information about line per se performance (LP) of inbreds and its relation to their general combining ability (GCA) is required. The objectives of our research were to (1) estimate variance components and heritability of LP for agronomic and quality traits relevant to biogas production, (2) study correlations among traits as well as between LP and GCA, and (3) discuss i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 18 publications
3
20
0
Order By: Relevance
“…The genetic material consisted of 289 maize inbred lines which were previously described in great detail [9,23-25]. The population constituted a global sample of elite breeding material from worldwide sources with a focus on North America and Europe and encompassed 285 lines from the Dent heterotic pool (Stiff-Stalk and non-Stiff-Stalk) and 4 from the European Flint pool, which served as check genotypes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The genetic material consisted of 289 maize inbred lines which were previously described in great detail [9,23-25]. The population constituted a global sample of elite breeding material from worldwide sources with a focus on North America and Europe and encompassed 285 lines from the Dent heterotic pool (Stiff-Stalk and non-Stiff-Stalk) and 4 from the European Flint pool, which served as check genotypes.…”
Section: Methodsmentioning
confidence: 99%
“…The population was phenotyped in six environments (three agroecologically diverse locations in the years 2008 and 2009) in Germany [25]. Briefly, the population was split into three maturity groups based on prior knowledge of their flowering time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study tested the biogas production of 57 different plant samples and concluded that a lignin (ADL) content of 10% was a critical threshold for high biodegradability in anaerobic digestion [237]. Also, a significant negative correlation between lignin content and methane production was observed in 285 different maize genotypes [266]. Several predictive models to estimate the biogas yield from lignocellulosic material include lignin as the major negative factor [267269].…”
Section: Role Of Lignin In the Bioenergy Sectormentioning
confidence: 99%
“…QTL mapping and marker assisted selection take advantage of the naturally occurring genetic variation in lignin content occurring within crop species [20, 266, 316, 317]. QTL associated with lignin content were reported for a number of crop species (Table 3).…”
Section: Lignin As a Target For Crop Breedingmentioning
confidence: 99%